'It Makes Me Feel Old': Understanding the Experience of Recovery From Ankle Fracture at 6 Months in People Aged 50 Years and Over. (March 2023) - Tutton, Elizabeth; Gould, Jenny; Lamb, Sarah E.; Costa, Matthew L.; Keene, David J.
Ankle fracture is a common injury, and depending on injury severity, treatment may be a support boot, cast or surgery. Older people, particularly those with severe injuries who are asked to restrict weight bearing, struggle with early recovery. To elicit older peoples' experience of recovery 6 months after injury, we drew on a phenomenological approach using interviews. Findings revealed that getting on with life was a way of accepting what it feels like to 'be vulnerable', needing to 'be safe' while determinedly working hard to 'be myself'. Being vulnerable identified endurance of inactivity, loneliness and dependency in the non-weight bearing period of recovery, followed by a struggle to weight bear while lacking confidence and being fearful of falling and causing further damage. Being safe conveyed fragility where sensations, pain and stiffness acted as bodily reminders of injury. Lack of function and awareness of danger led to carefulness where planning or curtailing of activities ensured their safety. Being myself showed a determination to push away from a disrupted self-identify of being older or disabled while being challenged by the continuous process of learning to be more mobile. A lack of readiness for old age created a drive to age well. Despite loss of ability, participants hoped to regain their pre-injury way of living. This study challenges practice that disregards the hard work required to recover from ankle fracture. As comorbidity increases with age, failure to consider this aspect may contribute to frailty in this group of older people.